Investigation of applied criteria for selecting online retailers: implications from the Indian market. (10th December 2021) - Kolte, Ashutosh; Sangvikar, Balkrishan; Pawar, Avinash; Singh, Jagbir
Today, online retail businesses focused on the adoption of customer centric approaches. Since the last few decades, information and internet technologies are providing new opportunities to businesses in market. Many retailers have started their online format of retailing called as e-retailing. This paper identifies the factors and criteria used by consumers to select online retailers for their consumption needs. The collected data of retailers is analysed using the statistical technique of interval estimates of the proportion. The outcome of the paper deliberates on the consumer factors for selecting online retailers which includes price range and quality, offers and discounts, payment methods and delivery options, and transparent return policy. Moreover, retailer image and trust, website, social media reports and customer reviews, privacy and security of data are crucial. Furthermore, a model of online retailing with criteria is proposed, which can help the retailers to operate in the Indian retail environment.